HUBUNGAN KEARIFAN LOKAL DENGAN NILAI-NILAI PANCASILA DALAM MEMBANGUN IDENTITAS DAN KARAKTER BANGSA DI SUKU DAYAK - Dwi Pratiwi, Mahdalena; Syakhira, Athia; Madison, Brigita Febbyana; Fauzi, Rizky; Azam, Mohammad Omar (Ganesha Civic Education Journal, 2026)
The state ideology of Pancasila plays a crucial role in shaping the nation’s character and identity. However, in the context of modernization, Pancasila values are often interpreted normatively without a strong connection to local indigenous cultural wisdom. This study aims to investigate how Pancasila values and identity and character. This study uses a qualitative approach with a literature review method to examine several scholarly sources on Dayak culture, social structures, and rituals, and their relationship to the five principles of Pancasila. The analysis findings indicate that the Dayak people’s spirituality, which respects the universe, aligns with Pancasila’s ideals of humanity and divinity. Furthemore, the equitable distribution of resources reflect the application of social justice princples that have been passsed down from generation to generation. In addition to its philosophical significance, the Law on Cultural Promotion and the 1945 Constitution of the Republic of Indonesia provide a legal basis for these ideas. Consequently, Dayak traditional knowledge is crucial as a contextual foundation for restoring Pancasila as a useful philosophy and strengthening national identity amidst the challenges of modernization.